Pengaruh Shopping Lifestyle, Fashion Involvement dan Discount Price terhadap Impulse Buying - Nicholas Randy Tjemara; Nurlinda Nurlinda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines and analyzes the effect of Shopping Lifestyle, Fashion Involvement, and Discount Prices simultaneously and partially on Impulse Buying in the Zalora Marketplace. And knowing which variables are most dominant in influencing impulse buying. The research approach used in this research is quantitative research. The criteria for selecting the sample in this study were those aged 17 and over who had used and made purchases through the Zalora Marketplace, and had routinely purchased products for the last 6 months through the Zalora Marketplace and were located in the Jabodetabek area. Questionnaires collected as many as 150 respondents, the data is then processed using multiple linear regression method. Based on the results of the analysis, it is known that the variables Shopping Lifestyle, Fashion Involvement and Discount Price simultaneously have a positive effect on Impulse Buying on the Zalora Marketplace. Partially, the Shopping Lifestyle and Fashion Involvement variables have a positive effect on Impulse Buying. But the Discount Price variable has no effect on impulse buying. Furthermore, the results show that the Shopping Lifestyle variable is the most dominant variable affecting Impulse Buying.